Hegel and the totality in the whole - Chaverri, Diego (2016)
Hegel ́s dialectical philosophy particularly unfolds in the concept of totality, one that allows apprehending the importance of other main concepts in his works. This article covers the concept of totality in Hegel thus pointing some of its implications beyond the German classical philosophy optimism, including his influence in sociology.